(3GdfhGOQ hGdRjGQGJ Ydi eG aj GdeOhfI hZjQgG ef GdCegGJs - (3YHO Gddg Hf YHO GdQMef GdfaRi GdbjQhGfi GdeGdcj , CHh eMeO , GHf CHi RjO , J (B386 (3g`s; (3CHh YHO Gddg YHO GdQMef Hf GdbGSe GdeGdcj, CHh YHO Gddg,J (B191 (3g` s
(3ChdgG (B:s
(3HGH GdMjV s
(3ef fSNI cJHJ ai GdbQf GdSGOSs
(3JHUQI GdYfhGf (B:s
(3JPjjds
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B10 - (3U (B282 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdabg GdeGdcjs